Plasmodium co-infection protects against chikungunya virus-induced pathologies - Teck-Hui Teo (Nature Portfolio, 2018)
Chikungunya virus (CHIKV) and Plasmodium co-infections have been reported in humans, but effects of the two pathogens on each other are unclear. Here, Teo et al. show in mice that Plasmodium infection affects CHIKV-specific T and B cell responses, leading to reduced joint inflammation.